Crystalline rock outcrops in the Atlantic Forest of northeastern Brazil: Vascular flora, biological spectrum, and invasive species - Gomes, Polyhanna [UNESP]; Sobral-Leite, Marcelo (Springer Nature, 2013)
We studied the vegetation of two crystalline rock outcrops in the Atlantic Forest of northeastern Brazil. We recorded typically rupicolous species, which are rare or classified as extremely endangered, such as Aechmea guainumbiorum, found exclusively in one of the study sites. In both areas there was a predominance of therophytes over other life-forms, in contrast to observations made in rock outcrops of the southern Atlantic Forest. Therophytes also stood out in other rock outcrops at similar latitudes as our study site, regardless of the surrounding vegetation. Plants of other life-forms had significantly lower richness and showed adaptations to drought, such as succulent stem, pseudobulbs, dense pilosity, and underground storage organs. Our results suggest that invasive species may modify the vegetation of crystalline rock outcrops, as they change the number of species of all life-forms in comparison between sites. Hence, our results present the biological identity of these rupicolous habitats, which are marginal to forests, and point to the need for conserving them, in order to protect the Atlantic Forest's biodiversity. © 2013 Botanical Society of Sao Paulo.
Keywords: Aechmea; Life-forms; Marginal habitats; Rupicolous habitats; Therophytes; Xerophytes